(untitled) (Central Asian Journal of Medical Sciences, 2022)
Objectives: This study examines the potential relationship between the incidence of dental caries in adults and the level of mucin-7 glycoprotein, a specific parameter in saliva. Methods: In a case-control study, samples of whole unstimulated saliva from 40 volunteers in two different groups were classified according to the decayed, missing, filled teeth (DMFT) index. One group was caries-free (n = 17), and the other had severe carries (n = 23). We measured the level of mucin-7, salivary buffer system, and pH and examined for relationships to the DMFT index. Results: There was a statistically significant difference among the groups (p < 0.001) in the level of mucin-7, salivary buffer system, and pH. The DMFT index for case and control groups was calculated as 0 and 14.09 ± 3.78. There was a strong, negative relationship between the level of mucin-7 and the DMFT index. Conclusion: The development of dental caries is linked to a reduced concentration of mucin-7 in saliva. The level of mucin-7 may be clinically useful for evaluating dental caries risk.